Unveiling the Gut Microbiota Landscape in Bangladeshi Female Breast Cancer Patients Through Next-Generation Sequencing (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Scientific evidence indicates that imbalances in the composition of gut microbiota are closely linked to the onset of many diseases. This study aimed to employ Next Generation Sequencing (NGS) to investigate gut microbial imbalances in Bangladeshi female breast cancer patients, enabling simultaneous analysis of numerous bacterial DNA fragments.  Materials and methods: In this case-control study, stool sample was collected from 30 cases of Bangladeshi female breast cancer patients and 30 female controls. Microbial genomic DNA was isolated to amplify targeted (V3-V4) region of the 16S ribosomal RNA (rRNA) gene. After indexing, NGS was done in Illumina sequencer using the MiSeq platform. Data were analyzed using QIIME and MiSeq Reporter to identify microbiome.  Results: Microbial differences were noted in Bangladeshi female breast cancer patients compared to the control group. At the phylum level (L2) 15 Operational Taxonomic Units (OTUs) were identified, fourteen phyla belonging to domain Bacteria and other to the domain Archaea. In the control group, bacteria belonging to phylum Firmicutes (44%) were dominant, were as in cases phylum Bacteroidetes were dominant. At the order level (L4) 53 OTUs were identified. In breast cancer and control groups, bacteria belonging to order Bacteroidales were dominant. In this research, gut microbial variation in Bangladeshi female breast cancer patients from that of controls was observed.  Conclusion: The emerging connection between the gut microbiome and female breast cancer could serve as a valuable lead for future research. Potential impact of gut microbiome would be further investigated for better management of female breast cancer patients. JCMCTA 2024 ; 35 (2) : 17-21